2020
DOI: 10.3390/toxins12020130
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Pet Food with Mycobiota and Fusarium Mycotoxins—Focus on Dogs and Cats

Abstract: A wide range of pet food types are available on the market; the dominant type is dry food formulated in croquets. One of the most common ingredients of dry food are cereals—vectors of harmful mycotoxins posing the risk to pet health. In this study, 38 cat and dog dry food samples available on the Polish market were investigated. Morphological and molecular methods were applied to identify fungal genera present in pet food. Quantification of ergosterol and Fusarium mycotoxins: Fumonisin B1, deoxynivalenol, niva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…They can also cause immunosuppression and hormonal disorders [ 2 , 9 ]. In addition, the few works on mycotoxins in pet food showed their high toxicity in relation to pets’ health [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…They can also cause immunosuppression and hormonal disorders [ 2 , 9 ]. In addition, the few works on mycotoxins in pet food showed their high toxicity in relation to pets’ health [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms present in cereals (bacteria belonging to the families: Pseudomonadaceae , Micrococcaceae , Lactobacillaceae , Bacillaceae , and fungi, like: Alternaria sp., Aspergillus sp., Cladosporium sp., Penicillium sp., Fusarium sp., Rhizopus sp.) can affect the safety, quality and functional properties of the grains and thus the quality of the dog food made from these cereals (Los et al 2018 ; Witaszak et al 2020 ). Thus, it can be assumed that the presence or absence of cereals in the food may affect the microbiological quality of the product.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was dog food that had higher percentage of contamination than the other tested foods. In one of the most recent studies, Witaszak et al ( 2020 ) isolated mycotoxigenic fungi belonging to five genus: Alternaria (7%), Aspergillus (12%), Cladosporium (10%), Penicillium (38%) and Fusarium (33%), from 38 cat and dog dry foods available on the Polish market. The traditional use of large amounts of plant ingredients (including cereals) by pet food producers, especially in dry product formulas, has greatly increased the risk of mycotoxin poisoning in pets (Boermans and Leung 2007 ), since the mycotoxins produced by some molds could potentially pose a health risk, in particular where the various stages of the pet food production process were not able to deactivate these fungal metabolites (Bullerman and Bianchini 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mycotoxins are secondary metabolites of fungi. They are commonly detected in food, feed [ 1 , 2 , 3 , 4 ], and feed additives [ 5 ]. The presence of mycotoxins in food and feed is influenced by numerous factors, including plant species and variety, region, temperature, moisture content, insect damage, storage conditions, and agricultural practices.…”
mentioning
confidence: 99%
“…An in vivo test also revealed that the presence of additional metabolites did not increase the overall toxicity. Witaszak et al [ 3 ] examined the presence of mycotoxins in dry food for dogs and cats. Their research was motivated by the fact that cereals are a major ingredient in dry food for companion animals.…”
mentioning
confidence: 99%